La Sociedad Del Conocimiento, La Educación Y La Tecnología - Navarro Angarita, Vanessa (Corporación Universitaria Americana, 2023)
Education is a complex phenomenon made up of multiple factors that interact simultaneously, since it involves the participation of all social actors. From the epistemological point of view, Education allows us to reflect on the educable nature of the human being; it studies the educational phenomenon from a rational and emotional point of view that delves into the person as a being linked to his environment, to society and to the culture to which he belongs.